2021
DOI: 10.3906/sag-2011-188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 pandemic on psychology and disease activity in patients with ankylosing spondylitis and rheumatoid arthritis

Abstract: Background/aim: The COVID-19 outbreak is known to increase stress levels of most patients with chronic diseases. Patients with Ankylosing Spondylitis (AS) and Rheumatoid Arthritis (RA) are highly susceptible to environmental stress. In the current study, we aimed to determine how the COVID-19 pandemic psychologically affected patients with chronic progressive diseases such as AS and RA and the effects of these psychological factors on disease activity.Materials and methods: Age and gender-matched patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
5
15
0
1
Order By: Relevance
“…The risk of depression was higher among patients with RDs with poorer perceived health as compared to their counterparts. This is similar to the reports that self-perceived worsening of the RD was a risk factor for depression during the pandemic [ 7 ]; that patients with RDs with comorbidities showed a higher rate of adverse mental health [ 5 ]; and that exacerbation of disease activities was associated with psychological status such as suicidal ideation and the ability to cope with trauma, anxiety, and depressive symptoms in patients with ankylosing spondylitis [ 12 ]. Ziadé et al [ 32 ] reported that people with poorer physical health have more severely restricted activities outside their homes, isolate themselves more, and display more severe symptoms of depression, suggesting that patients with poorer perceived health are at a higher risk for depression than their counterparts.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The risk of depression was higher among patients with RDs with poorer perceived health as compared to their counterparts. This is similar to the reports that self-perceived worsening of the RD was a risk factor for depression during the pandemic [ 7 ]; that patients with RDs with comorbidities showed a higher rate of adverse mental health [ 5 ]; and that exacerbation of disease activities was associated with psychological status such as suicidal ideation and the ability to cope with trauma, anxiety, and depressive symptoms in patients with ankylosing spondylitis [ 12 ]. Ziadé et al [ 32 ] reported that people with poorer physical health have more severely restricted activities outside their homes, isolate themselves more, and display more severe symptoms of depression, suggesting that patients with poorer perceived health are at a higher risk for depression than their counterparts.…”
Section: Discussionsupporting
confidence: 85%
“…As patients with RDs must adapt to their disease and comply with treatment regimens for the rest of their lives, depression is a common mental health disorder observed in this population owing to increased disease activity, suboptimal treatment adherence, reduced treatment response, and decreased quality of life [ 8 , 9 ]. Fear of health risk, stress, social isolation [ 10 ], anxiety [ 11 ], disease activity [ 12 ], physical symptoms [ 13 ], and insomnia [ 14 ] during the current pandemic can elevate the risk of depression or exacerbate depression symptoms among patients with RDs. Prior studies have reported that the unprecedented changes in the social environment caused by social distancing, restricted social gatherings, working from home, online-centered lifestyle, and quarantine during the pandemic posed serious mental health threats to patients with RDs.…”
Section: Introductionmentioning
confidence: 99%
“…All rights reserved. (9), do not know (8), missing (5) *If yes to positive test (n=424), did you still have symptoms >4 weeks after testing (>1 answer allowed): no (105), tiredness (204), reduced/loss of smell (138), shortness of breath (108), headache (107), arthralgia (103), muscle pain (94), concentration reduced (92), altered sensation (16), heart disease (7), blood clots (3), do not know (24), not relevant (14) *if yes to symptoms >4 weeks after testing (n=281), what is the current status: recovered (121), still some problems (114), still many problems (38), not relevant (4), do not know (2), missing (2)…”
Section: Contributorsmentioning
confidence: 99%
“…A recent report highlighted the positive relationship between perceived COVID threat and psychological status with the disease activity among AS patients. [4] However, with emerging knowledge in this domain and new scientific technologies, it is noteworthy how the role of intervention such as exercise, physiotherapy, and mind-body medicine are delineating to be an efficient adjunct in treating AS. [5] , [6] The previous study suggests an improvement in the Bath Ankylosing spondylitis disease activity index (BASDAI) by 32%,advocating the effectiveness of yoga and physiotherapy intervention in these patients.…”
Section: Introductionmentioning
confidence: 99%